Response to Vegetative Growth of Soybean (Glycine Max) Variety of Anjasmoro and Demas 1 to Giving Trichoderma Sp. on the Check of Salinity - Zainur Rochman; Sutarman (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the response of the vegetative growth of soybean (Glycine max) of Anjasmoro and Demas varieties to the application of Trichoderma sp. Compost. on salinity stress. This research was conducted in the dry land of the swamp of Jabon Village, Sidoarjo, from March to May 2020. The experiment was arranged factorial using a Randomized Block Design consisting of two factors, namely: the first factor was soybean varieties consisting of: varieties. Anjasmoro, and Demas 1 varieties, while the second factor was the application of Trichoderma compost consisting of: without Trichoderma and with Trichoderma. Of the 4 treatment combinations were repeated 5 times, in order to obtain 20 experimental units, each containing 40 plants. Data were analyzed by ANOVA followed by the 5% HSD test. The results showed that there was a significant interaction effect between the varieties and the application of Trichoderma sp. on the growth rate of sprouts and the number of leaves grown on land with an average salinity of 4 dS.cm-1 at 35 days after planting. Anjasmoro variety shows tolerance on saline soil, while Demas 1 variants are intolerant to saline soil. Anjasmoro varieties treated with Trichoderma sp. compost were able to show a sprout growth rate of up to 6.10 cm per day and accelerate the appearance of flowers on high salinity soils. The combination of these two has the potential to be tested and developed into a wide production stage on high salinity swamps.